Investigation of the safety factor and reliability of the embankment in soil cement column improved ground on Saga lowland - Y. Jabeur; S. Manandhar; S. Shrestha; T. Hino; M. Mbodji; T. Himeno (International Association of Lowland Technology, 2019)
Saga plain constitutes thick deposited soft marine clay which is susceptible for the construction of any civil engineering structures with reference to large and differential settlement problems in the area. This paper presents the case study of the Ariake sea coastal road project failure on Ashikari region in Saga lowland. In this region, the group of soil cement columns as ground improvement technique is adopted for the construction of the highway embankment. The estimation of probability of failure of the embankment on the stabilized soils is approached through the probabilistic analysis for this research. The assessments of total safety factor (Fs) and reliability rely on random variables of geotechnical parameters. These random variables considered for this study are the unit weights of the soil materials (γ) (fill and clay), the undrained shear strength (cu) in the embankment fill material and undrained shear strength of the stabilized soil and soft soil. Furthermore, the paper also delineates judgment of the geotechnical risk assessment based on real site condition.